1988
DOI: 10.1063/1.99925
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of stable species present during filament-assisted diamond growth

Abstract: We have measured mole fractions of two of the major stable species at the surface of a silicon substrate during filament-assisted diamond growth as a function of the filament-to-substrate distance. Input gases were methane and hydrogen. A quartz probe withdrew gases at the growing surface, and the gases were sampled with an on-line mass spectrometer. Close to the filament the methane is largely consumed, with most of the remaining gas phase carbon in the form of acetylene. Mass spectral results are compared to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
56
0

Year Published

1991
1991
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 229 publications
(62 citation statements)
references
References 17 publications
6
56
0
Order By: Relevance
“…There have been many studies of the gas-phase chemistry during diamond CVD [58][59][60][61][62][63][64][65][66][67][68]. These investigations revealed that atomic hydrogen and hydrocarbon are perhaps the most critical determinants of CVD diamond as well as its quality and growth rate.…”
Section: The Gas-phase Chemical Environmentmentioning
confidence: 99%
See 1 more Smart Citation
“…There have been many studies of the gas-phase chemistry during diamond CVD [58][59][60][61][62][63][64][65][66][67][68]. These investigations revealed that atomic hydrogen and hydrocarbon are perhaps the most critical determinants of CVD diamond as well as its quality and growth rate.…”
Section: The Gas-phase Chemical Environmentmentioning
confidence: 99%
“…At 20 Torr, the characteristic time for this reaction is in the order of 1 sec [59,60]. In time t an atom may diffuse a distance of order Dt , where D is the diffusion coefficient.…”
Section: Atomic Hydrogenmentioning
confidence: 99%
“…Considerable research in the field has been aimed at determining the "growth" species, i.e., the gas phase species directly responsible for diamond formation [11,121, and recent experiments have demonstrated that the CH 3 radical is the primary growth species in the CVD systems that have been examined [13][14][15][16][17][18][19]. One proposed chemical kinetics mechanism [21, which takes CH 3 as the growth species, successfully predicts [20][21][22], experimental growth rates for both RF [211 and DC [23] plasma torches, for flames at low and atmospheric pressure [15,24,25], and for filament systems as a function of pressure and composition [16,17], without the use of adjustable parameters.…”
Section: Introductionmentioning
confidence: 99%
“…It is found that this range of residence time does not allow the flow to reach equilibrium at the reactor condictions. For similar residence times, temperatures and pressures, it has been found that mixtures of methane and hydrogen in thermal vapor deposition systems used to grow diamond films also falls short of reaching equilibrium gas-phase conditions [15,16,17].…”
Section: Kinetic Mechanismmentioning
confidence: 99%